Evolutionary processes and organizational adaptation : a Mendelian perspective on strategic management - Levinthal, Daniel A. (Oxford scholarship online., 2021)
How do firms adapt? Is it through rational choice and intentionality, or rather a process of evolutionary dynamics? Using the ideas of Gregor Mendel as a touchstone, this book constructs a middle-ground between these two conceptions and provide a new framework for understanding the adaptive dynamics of organizations.